Research progress of exosomes in orthopedics - Zhang, Liang; Lin, Yi; Zhang, Xiannan; Shan, Chen (Frontiers in Genetics, 2022)
Exosomes are nano-extracellular vesicles secreted by a variety of cells. They are composed of double-layer membrane which can transport a variety of proteins, coding and non-coding genes, and bioactive substances. Exosomes participate in information transmission between cells and regulate processes like cell proliferation, migration, angiogenesis, and phenotypic transformation. They have broad prospects in the occurrence, development, and treatment of many diseases including orthopedics. Exosomes derived from different types of bone cells such as mesenchymal stem cells, osteoblasts, osteoclasts and their precursors are recognized to play pivotal roles in bone remodeling processes including osteogenesis, osteoclastogenesis, and angiogenesis. This paper summarizes the characteristics of exosomes and their research progress in in bone remodeling, bone tumors, vascular skeletal muscle injury, spinal cord injury, the degenerative disc diseases, cartilage degeneration, osteoarthritis, necrosis of femoral head and osteoporosis.